Colorectal cancer with peritoneal carcinomatosis in a teenager - Shuji Nakamoto; Kiyoshi Tanaka; Eiichiro Watanabe; Noriko Takeda; Takatoshi Nakamura; Yusuke Kumamoto (Elsevier, 2020)
Colorectal cancer is a rare disease in children. It is often diagnosed at an advanced stage, meaning that these patients often require a multidisciplinary treatment approach. This is a case report of advanced cecal cancer in a teenager who was treated with cytoreductive surgery and long-term chemotherapy with molecular targeted agents.A previously healthy 15-year-old boy was referred to our hospital with a two-month history of abdominal pain and diarrhea. On physical examination, his abdomen was distended and a tender mass was palpable in the right lower quadrant. Laboratory data revealed severe anemia and elevated tumor markers. Computed tomography showed thickening of the cecal wall and multiple peritoneal nodules. He was diagnosed with advanced cecal cancer with peritoneal metastasis, and underwent right colectomy, followed by 5-fluorouracil-based chemotherapy with molecular targeted agents. However, his disease continued to progress, and the patient died 17 months after his initial diagnosis.The rarity of this disease means diagnosis is difficult and that there is little evidence on best treatment; therefore, more research is needed in these areas. Keywords: Colorectal cancer, Peritoneal carcinomatosis, Pediatrics